EXPERIMENTAL STUDY ON HYBRID MAGNESIUM COMPOSITES FOR HUMAN BONE IMPLANTS - V.K Neela Murali; Starvin M S (Journal of the Chilean Chemical Society, 2023)
The hybrid Magnesium composite having alloying elements zinc, manganese with the reinforcement of nano TiO2 and micron level Al2O3 was prepared through hot press sintering method. This study is primarily determined the effect of reinforcing multi ceramic particles in the Mg composites for their mechanical and corrosion strength to validate the human bone implants. The scanning electron microscopy and X-ray diffractogram were used to analyze the micro structural variation on the hybrid composites. The microstructural study showed that, many intermetallic phases were formed during the composite preparation process which reduces the porosity and increases density of the composites. The reinforced particles, manufacturing process and after heat treatment or stress reliving process were enhanced the mechanical and corrosion strength of the prepared hybrid composites.